Development of paediatric oncology shared-care networks in low-middle income countries. (June 2018) - Burns, Elizabeth; Collington, Meg; Eden, Tim; Freccero, Piera; Renner, Lorna; Paintsil, Vivian; Dolendo, Mae; islam, Afiqul; Khaing, Aye Aye; Rosser, Jon
Highlights: Traditionally single centre childhood cancer centres have been created in developing countries. To optimise access for all children networks of a hub centre with shared care units is recommended. Networks require good communication, a common purpose, agreed guidelines and staff training. Increased awareness of cancer and its curability if diagnosed early results from this strategy. Community and Government support for networks is essential for success. Abstract: In order to reach out and offer optimum access for children with cancer across each country the development of networks of paediatric oncology units rather than just a single centre in one city has been the practice in high income countries over the last 30–40 years and is now being considered by developing countries. At a workshop bringing delegates from 4 countries in Africa and Asia to share their concepts, ideas and experiences of developing such networks and how to move forward, it was recommended that there should be a Hub (referral centre), shared-care centre hospitals, a real emphasis on good communication, ability to train staff within the network and a focus on ensuring that each hospital and country's government must be supportive for it to be successful.